An analysis of weight loss articles and advertisements inmainstream women's health and fitness magazines - Danna Ethan; Corey Basch; Grace Hillyer; Alyssa Berdnik; Mary Huynh (Tabriz University of Medical Sciences, 2016)
Background: Magazines are a commonly used source for health and fitness information. Little is known about the nature and extent of weight loss strategies and products presented in mainstream women's health and fitness magazines. Methods: This preliminary cross-sectional study evaluated the prevalence of articles and advertisements featuring weight loss content and products in mainstream US-based health and fitness magazines, as well as assessed weight loss themes presented. Thirty-one US health and fitness-focused magazine issues were coded. Prevalence of, product type, and themes related to weight loss in articles and advertisements were assessed. Results: Among the 31 issues of the five US-based women's magazines examined, we identified 39 articles (4.8% [95% CI = 3.3% to 5.5%] of 819 articles) related to weight loss with 14 identified weight loss topics. The most prevalent article topics covered were exercising/workouts(32.0% [95% CI = 28.8% to 33.6%]) followed by dieting (18.6% [95% CI = 15.9% to 19.9%]).The most common product advertised was weight loss pills (46.0% [95% CI = 42.6% to 47.7%]).Fat burners were also frequently advertised (14.9% [95% CI = 12.5% to 16.1%]) followed by hunger reduction strategies (10.3% [95% CI = 8.2% to 11.3%]) and fat blockers (6.9% [95% CI= 5.2% to 7.8%]). Conclusion: Articles presented information about exercise and dieting whereas advertisements supported potentially harmful health beliefs and behaviors. As a well-utilized American media format, health and fitness-focused magazines have an opportunity to communicate frequent,accurate messaging about healthy weight reduction and limit advertisements that may include misleading claims.